Influence of Employee Engagement, Work-Life Balance, and Career Development on the Psychological Resilience of Regional Financial Agency Employees - Monalisa Hastarina; Wazirman (Jurnal Informatika Ekonomi Bisnis, 2026)
This study aims to analyze the influence of employee engagement, work-life balance, and career development on the psychological resilience of employees of the Regional Finance Agency (Bakeuda) of Sungai Penuh City, both partially and simultaneously. Employee psychological resilience is an individual's ability to survive, adapt, and remain productive in the face of work pressure and demands. This study uses a quantitative approach with a survey method, where data are collected through distributing questionnaires to Bakeuda employees of Sungai Penuh City. The obtained data are analyzed using multiple linear regression analysis to test the influence between research variables. The results show that employee engagement, work-life balance, and career development have a partial positive and significant effect on employee psychological resilience. Simultaneously, these three variables also have a significant effect on psychological resilience, as evidenced by the F test significance value of 0.000 (